The Predictive Value of Myoglobin for COVID-19-Related Adverse Outcomes: A Systematic Review and Meta-Analysis - Ma, Chaoqun; Tu, Dingyuan; Gu, Jiawei; Xu, Qiang; Hou, Pan; Wu, Hong; Guo, Zhifu; Bai, Yuan; Zhao, Xianxian; Li, Pan (Frontiers in Cardiovascular Medicine, 2021)
Objective: Cardiac injury is detected in numerous coronavirus disease 2019 (COVID-19) patients, and has been demonstrated to be closely related to poor outcomes. However, an optimal cardiac biomarker for predicting COVID-19 prognosis has not been identified. Methods: The PubMed, Web of Science and Embase databases were searched for published articles between December 1, 2019 and September 8, 2021. Eligible studies that examined the anomalies of different cardiac biomarkers in COVID-19 patients were included. The prevalence and odds ratios (ORs) were extracted. Summary estimates and the corresponding 95% confidence intervals (95% CIs) were obtained through meta-analyses. Results: A total of 63 studies with 64,319 COVID-19 patients were enrolled in this meta-analysis. The prevalence of elevated cardiac troponin I (cTnI) and myoglobin (Mb) in the general population with COVID-19 was 22.9% (19.0-27.0%) and 13.5% (10.6-16.4%), respectively. However, the presence of elevated Mb was more common than elevated cTnI in severe COVID-19 patients [37.7% (23.3-52.1%) vs. 30.7% (24.7-37.1%)]. Moreover, compared with cTnI, the elevation of Mb also demonstrated tendency of higher correlation with case-severity rate (Mb, r=13.90 vs. cTnI, r=3.93) and case-fatality rate (Mb, r=15.42 vs. cTnI, r=3.04). Notably, elevated Mb level was also associated with higher odds of severe illness [Mb, OR=13.75 (10.20-18.54) vs. cTnI, OR=7.06 (3.94-12.65)] and mortality [Mb, OR=13.49 (9.30-19.58) vs. cTnI, OR=7.75(4.40-13.66)] than cTnI. Conclusions: COVID-19 patients with elevated Mb levels are at significantly higher risk of severe disease and mortality. Elevation of Mb may serve as a marker for predicting COVID-19-related adverse outcomes.